A financial evaluation of RFID technology in sheep feedlots - De Wet, Pieter-Steyn (University of the Free State, 2018)
Agricultural producers are confronted with a wide range of challenges early in the third millennium. Population growth and changing consumption patterns will cause world food, feed and biofuel requirements to more than double by 2050 and will require sustainable solutions. South Africa also faces these challenges with the population predicted to increase further, and the demand for mutton is predicted to increase by 5% between 2016 and 2026. This poses a challenge to the local sheep producers in South Africa to meet the growing demand. The implementation of digital systems will greatly improve the way producers use the resources available to produce the required amount of food for the growing population. Precision agriculture technology is paving the way for South African agricultural producers to manage inputs more precisely. One of the latest additions to the South African precision farming tools is the use of radio frequency identification (RFID) systems. However, the available precision farming research investigating these technologies and systems has mostly focused on the crop industry. Limited precision research has focused on the livestock industry, especially on the South African sheep feedlot industry. The aim of this study was to evaluate the financial viability of implementing RFID technology in a South African sheep feedlot. This study is based on data that was collected from a sheep feedlot in the Western Cape province of South Africa. The sample size comprised 508 lambs supplied from 35 different producers. In the study, two feedlot scenarios were created to investigate the monetary benefit that a RFID system would hold for an investor. The analysis of the first scenario was done by drafting (removing) non-performing animals from the feedlot on day 14 to determine how much feed can be saved by culling them early on in the feedlot cycle. The analysis of the second scenario was done by identifying the worst third of the suppliers after a one-year test period based on the performance of their lambs. From year 2 onwards, the feedlot only bought lambs from the top two-thirds of suppliers. Besides only purchasing lambs from these top suppliers, the RFID system continued drafting non-performing animals based on their performance up to day 14 in the feedlot. By drafting the non-performing animals and suppliers, a monetary value could be placed upon the management benefits provided by the system to the investor. The cash flows of each of the scenarios were measured with selected financial indicators to determine the viability of investing in a RFID system. The financial indicators indicated that investment in a RFID system should only be considered under the condition of scenario 2, in which the information gathered by the system was used to identify better performing suppliers of lambs. If the only purpose of investing in a RFID system is to draft animals during their feedlot period, it should not be considered. The model developed in this study contributes to the knowledge base of the South African sheep feedlot industry. It is a convenient instrument to assist sheep feedlots in decision making regarding an investment in RFID technology.
Dissertation (M.Agric. (Agricultural Economics))--University of the Free State, 2018
Keywords: RFID; Feedlot; Meat; Traceability; Technology; Producer; Capital; Investment; Lamb